Intra–Abdominal Desmoplastic Small Round Cell Tumor: A Rare Case Report and Review of Literature - Ankur Mudgal; Devender Sharma; Vikram Singhal; Ashok Vaid (Indian Journal of Medical and Paediatric Oncology)
Desmoplastic small round cell tumor (DSRCT) is a rare and aggressive type of sarcomatous tumor with a high proclivity ofmetastasis.While it predominantly affects the abdominal cavity, it is most often observed in younger males and histopathologically identified by vascular and collagenous stroma containing groups of small tumor cells. However, standardized treatment approaches are currently unavailable. Here, we present the case of a 47-year-old man diagnosed with intra-abdominal metastatic DSRCT managed with multiple lines of chemotherapy followed by surgical debulking. Overall survival of 32 months is achieved with good quality of life.